Evaluation of African yam bean (Sphenostylis stenocarpa) accessions grown in Togo for nutritional and antinutritional properties - Palanga, Koffi Kibalou; Ahonon, Awovi Selom; Bawa, Anissou; Batchazi, Koffi; Modom Banla, Essohouna; Akabassi, Ghislain Comlan; Souho, Tiatou (Frontiers in Food Science and Technology, 2025)
IntroductionAfrican yam bean (AYB) is a native legume crop from Africa with significant nutritional and health potential. In Togo, however, the crop remains underutilized and neglected due to a lack of awareness of its substantial potential. This study aimed to analyze seeds from different accessions of AYB cultivated in Togo in order to compare their biochemical properties and identify superior genotypes that could be promoted in the Togolese population's diet through direct consumption or food fortification.MethodsTwenty-two accessions of AYB cultivated in Togo were profiled for their nutritional composition, antinutritional factor content, and mineral composition.Results and DiscussionThe accessions were grouped into five clusters: cluster II was prominent with 11 accessions, while cluster V had only one accession. Accessions HIA A10, HIA A13, HIA A14, HIA A28, HIA A39, HIA A68, HIA A84, HIA A2, HIA A75, and HIA A87 exhibited desirable levels of nutrients such as protein, fiber, Mg, and Fe, which could be exploited for the further development of AYB in Togo. Correlation analysis revealed low to moderate positive and significant (P < 0.05) association between some parameters such as Mg and Vit C or P and Ca indicating that such parameters could be simultaneously selected during programs aimed at improving the nutritional quality of AYB accessions.